Analysis of the impact of training on the performance of Small and Medium-sized enterprises in Northwest Mexico, by applying the Structural Equations Statistical Technique (SEM-PLS) - Vasquez-Torres, Maria del Carmen; Salazar, Arturo Tavizon (Zielona Góra: Faculty of Economics and Management Press)
Small and medium enterprises (SMEs) are fundamental to the economy of all countries, representing the majority, with a considerable contribution to GDP, as well as generating jobs; for this reason, it must seek to remain in the market.
Keywords: small and medium-sized enterprises; training; performance; organization; development; SME; MSP; małe i średnie przedsiębiorstwa; szkolenia; wydajność; organizacja